Implementasi Kebijakan Identitas Kependudukan Digital (IKD) di Desa Tunggalpager Kecamatan Pungging Kabupaten Mojokerto - Tauran; Tjitjik Rahaju; Indah Prabawati; Novika Rahmawati (Universitas Negeri Surabaya, 2026)
Population identity is necessary to ensure orderly administration. The Indonesian government, through Minister of Home Affairs Regulation No. 72 of 2022 concerning Standards and Specifications for Hardware, Software, and Electronic Identity Card Forms and the Implementation of Digital Population Identity, launched the IKD application as a solution to facilitate service access and data security. However, policy implementation at the village level, particularly in Tunggalpager Village, has low public awareness, resulting in targets not being met. This study aims to analyze the implementation of the IKD Program policy in Tunggalpager Village. The research method used qualitative descriptive methods through observation, interviews, and documentation. It uses George C. Edward III's implementation theory with four main indicators: communication, resources, disposition, and bureaucratic structure. The results show that the implementation of the IKD policy in Tunggalpager Village has not been optimal. Communication, information between implementers are optimal, but the community is hampered by low digital literacy and a lack of active outreach. Resources are limited due to the presence of only one operator, limited access to SIAK, and a lack of facilities such as laptops and supporting facilities. Disposition of the implementers shows good commitment, but the absence of coercive policies results in weak community support, and the incentives provided are not a determinant of program success. Bureaucratic structure, SOPs are aligned with the central government's. However, fragmented data security reduces service flexibility. In conclusion, the implementation of the IKD in Tunggalpager Village is hampered by limited resources, the need for active outreach, additional staff, and policies related to access restrictions to expedite the IKD process.